Adventures in the solar system : Planetron and me - Williams, Geoffrey T. (Los Angeles : Price/Stern/Sloan, 1986)
A young boy takes a voyage through the solar system aboard a space ship and learns about the sun, planets, moons, and asteroids.
Keywords: Interplanetary voyages -- Fiction; Solar system -- Fiction; Outer space -- Exploration -- Fiction